Case report: Unraveling a unique case of male occult breast cancer with axillary intricacies and a comprehensive literature dive - Xie, Xintong; Kong, Xiangyi; Jiang, Hongnan; Gao, Jidong (Frontiers in Oncology, 2025)
Male breast cancer is a rare neoplasm, accounting for approximately 1% of all breast cancer cases. It typically presents as a painless, retroareolar mass. An exceedingly rare variant is male occult breast cancer, which is primarily characterized by axillary lymph node enlargement without an identifiable primary breast tumor. We report an intriguing case of a septuagenarian patient diagnosed with male occult breast cancer. The patient presented with both axillary lymph node enlargement and an associated axillary skin ulcer, and was subsequently diagnosed with male occult breast cancer with metastases to the axillary and clavicular lymph nodes, as well as more distant sites. His treatment involved a multidisciplinary approach, including HER2-targeted therapy, chemotherapy, axillary lymph node dissection, and radiotherapy. Regular follow-ups have shown that his condition remains stable. Notably, this is the first documented case of male occult breast cancer with distant metastasis that was successfully treated with surgery and radiotherapy following systemic therapy. This case highlights the complex clinical presentation and management of male occult breast cancer. Our findings suggest that surgical intervention may be a feasible option post-downstaging by systemic therapy, even in the presence of distant metastases.